INSUFICIENCIA NORMATIVA EN EL ART. 84 DE LA LEY DE DEFENSA DEL CONSUMIDOR, QUE NO PREVÉ EL ANUNCIO DE PRUEBA, AFECTA LA GARANTÍA DEL DERECHO A LA DEFENSA CONTEMPLADO EN LA CONSTITUCIÓN EN EL ART. 76 NUMERAL 7, INCISO H - Abad Alverca, Antonio Geovanny (2016)
This research theme is made on the problems that exist concerning the absence of a term annunciation of evidence, oral hearing before the trial. For the development of this paper set out to conduct a general objective theoretical, legal and critical study of regulatory failure of art. 84 of the Law on Consumer Protection to ensure the right to defense to present evidence and contradict those submitted against him at the right time, which was verified by the application of methods and techniques of scientific, I they led to the conclusion that enabled results support the law reform proposal. More than bibliographic doctrinaire collection, thirty were surveyed people who know the subject that is in the problem, plus three interviews with people in keeping with the theme in relation to their profession and their role in the environment and is an Violations judge, a legal professional and a representative of Consumers' Association of this city, these data were collected, it was concluded that there is indeed a loophole which directly affects the litigants when time to review the evidence to be presented by the counterparty, which causes problems in society that sometime feels harmed by a product, therefore field research showed we consider it essential to increase a term of oral evidence before the trial hearing through an amendment to the Organic Law on Consumer Protection, in order to ensure better defense between the parties, in compliance with due process and fulfilling the principle of contradiction as required by the Constitution of the Republic of Ecuador